2011
DOI: 10.1002/ibd.21611
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of hath1 gene expression directly regulated by hes1 via notch signaling is associated with goblet cell depletion in ulcerative colitis

Abstract: The present study suggests that Hes1 is essential for Hath1 gene suppression via Notch signaling. Moreover, the suppression of Hath1 is associated with goblet cell depletion in UC. Understanding the regulation of goblet cell depletion may lead to the development of new therapy for UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
91
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(98 citation statements)
references
References 30 publications
6
91
1
Order By: Relevance
“…However, our in vitro data showed that all unsaturated FAs tested (OA, LA, ALA, EPA, and GLA) induced drastic decreases in the expression of HATH1, a basic helix-loop-helix transcription factor that plays a key role in the differentiation of goblet cells (43). Indeed, the intestinal epithelium is characterized by its rapid and constant renewal from multipotent stem cells located near the base of the crypt.…”
Section: Discussionmentioning
confidence: 88%
“…However, our in vitro data showed that all unsaturated FAs tested (OA, LA, ALA, EPA, and GLA) induced drastic decreases in the expression of HATH1, a basic helix-loop-helix transcription factor that plays a key role in the differentiation of goblet cells (43). Indeed, the intestinal epithelium is characterized by its rapid and constant renewal from multipotent stem cells located near the base of the crypt.…”
Section: Discussionmentioning
confidence: 88%
“…HES5 targets the Atoh1 promoter region for repression bHLH proteins of the Hes/Hey family have been shown to bind a canonical N-box (CACNAG) or C-site (CACGNG) in their target genes Grogan et al, 2008;Zheng et al, 2011). In addition to the N-box and a C-site in the 3′ enhancer, the Atoh1 promoter contains four highly evolutionarily conserved sites within 226 bp of the transcription start site ( Fig.…”
Section: Derepression Of Atoh1 Is Sufficient To Induce Atoh1 Transcrimentioning
confidence: 99%
“…Although the general cell lineages of the intestine are regulated by a series of transcriptional factors [20], it remains unknown how the ratio of the respective cell lineages are regulated in each villus. In particular, the gene expression profiling is longitudinally different throughout the entire small intestine without Notch signal influence [21], although the differentiationdetermined transcriptional factor Atoh1 was directly repressed by Hes1 via Notch signal [22]. This finding suggested that the comportment of stem cells with permanent lineage directivity in a crypt might be changed to adjust the proper cell distribution.…”
Section: Discussionmentioning
confidence: 95%